Is bigger necessarily better in community banking? - Joseph P. Hughes; Julapa Jagtiani; Loretta J. Mester (Rutgers University, Department of Economics, 2016)
We investigate the relative performance of publicly traded community banks (those with assets less than 10 billion) versus larger banks (those with assets between 10 billion and 50 billion). A body of research has shown that community banks have potential advantages in relationship lending compared with large banks, although newer research suggests that these advantages may be shrinking. In addition, the burdens placed on community banks by the regulatory reforms mandated by the Dodd-Frank Wall Street Reform and Consumer Protection Act and the need to increase investment in technology, both of which have fixed-cost components, may have disproportionately raised community banks costs. We find that, on average, large banks financially outperform community banks as a group and are more efficient at credit-risk assessment and monitoring. But within the community bank segment, larger community banks outperform smaller community banks. Our findings, taken as a whole, suggest that there are incentives for small banks to grow larger to exploit scale economies and to achieve other scale-related benefits in terms of credit-risk monitoring. In addition, we find that small business lending is an important factor in the better performance of large community banks compared with small community banks. Thus, concern that small business lending would be adversely affected if small community banks find it beneficial to increase their scale is not supported by our results.
Keywords: G21; L25; 330; community banking; scale; financial performance; small business lending